Immune Microenvironment of Brain Metastases—Are Microglia and Other Brain Macrophages Little Helpers? - You, Hua; Baluszek, Szymon; Kaminska, Bozena (Frontiers in Immunology, 2019)
Brain metastases are common intracranial neoplasms and their frequency increases with prolonged survival of cancer patients. New pharmaceuticals targeting oncogenic kinases and immune checkpoint inhibitors increase overall and progression-free survival in patients with brain metastases, but fail to reduce metastatic burden and still a majority of oncologic patients die due to dissemination of the disease. Despite therapy advancements, median survival of patients with brain metastases remains six months. The role of the innate immune system in cancer development and progression is well established. Tumor-associated macrophages (TAMs), instead of launching antitumor responses, promote extracellular matrix degradation, secrete immunosuppressive cytokines, promote neoangiogenesis and tumor growth. While their roles as pro-tumorigenic cells facilitating tissue remodeling, invasion and metastasis is well documented, much less is known about the immune microenvironment of brain metastases and roles of specific immune cells in those processes. The central nervous system (CNS) is armed in resident myeloid cells: microglia and perivascular macrophages which colonize CNS in early development and maintain homeostasis in brain parenchyma and at brain-blood vessels interfaces. In the current study we discuss available data on the immune composition of most common brain metastases, focusing on interactions between metastatic cancer cells and microglia, perivascular and meningeal macrophages. Cancer cells ‘highjack’ several CNS protective mechanisms and employ microglia and perivascular macrophages into helping cancer cells to extravasate and colonize a pre-metastatic niche. We describe emerging molecular insights into mechanisms governing interactions between microglia and metastatic cancer cells that lead to microglia activation and trafficking of monocytic cells from the periphery. We present mechanisms controlling those processes in brain metastases and hypothesize on potential therapeutic approaches. In summary, microglia and non-parenchymal macrophages are involved in multiple stages of a metastatic disease and, unlike tumor cells, are genetically stable and predictable, which makes them an attractive target for anticancer therapies.